EMPLEO CON PROFESIONALIZACIÓN EN EL SECTOR TURISMO - Granados Maguiño, Mauro Amaru (2010)
Part of the problem is that a low quality employment in the tourist sector involves proportionally equal quality in the service. It is also a problem low global productivity of the sector and an imminent risk for its development in a context marked by an increasing competition. If the labor mass is not qualified adequately, the level of the service will be deficient; that is why it is necessary high levels of professionalization and workers have received formal and academic training in major proportion.